IT Changes in Management in the Face of the Global Crisis and Pandemic - Jerzy WACHOL (Communications of International Proceedings, 2021)
This study presents knowledge and multimedia as the basic drivers of success in pursuit of a specific goal of activity in the given time and place part of globalisation and computerisation processes. It is based on global economic data, literature and own experiences of the author, presents practical assumptions for the system for collection, selection, processing and analysis of information for the purpose of creation of the currently needed knowledge. It also presents own studies. The purpose of the study is depicting knowledge and multimedia systems, including IT, as the basic driver of economic success in the times of globalisation, pandemic, economic crisis and the age of IT. State-of-the-art knowledge, modern technologies are usually very expensive and, thus, it is usually the richest big organisations who can afford them. It is usually the birthplace of the latest knowledge and modern technologies which, when applied in the economy, can bring an advantage over the competition and, thus, potential big economic success. Scientific and technological accomplishments, also in IT, of one country can be used in the industry of another, even distant country, and skilful use of available knowledge is becoming a must for survival. Over time, knowledge and technology once discovered as well as experiences become popularised in the entire world and right storage of these accomplishments allows also to transfer them in time. Success requires practical assumptions for the system for collection, storage, selection, processing and analysis of information for the purpose of creation of the currently needed knowledge. Global data show that accomplishing economic success usually goes hand in hand with state-of-the-art technologies and skilful use of multimedia means, including - first and foremost - computers, networks and IT systems, even in the times of the pandemic and crisis.
Keywords: IT; networks; computerisation processes; management; pandemic; globalisation; economic crisis; knowledge; multimedia systems.